2020
DOI: 10.1007/7854_2020_162
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition and the Suicidal Process

Abstract: Early thinking about cognitive process and suicidal behaviors tended to focus on the immediate situation surrounding the individualtypically the underlying psychiatric condition that was seen as leading to his or her distress. However, we now know that the cognitive processes involved in a range of suicidal thoughts and behaviors can exert a significant impact on the expression or development of these behaviors, even without an environmental stressor or psychiatric condition. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 189 publications
0
3
0
Order By: Relevance
“…In our study, in the most of these tests measuring episodic memory and learning, it was observed that, the number of correct responses in adolescents with depression was significantly lower than that of healthy controls, and they answered questions more slowly. Our findings are consistent with the broad literature suggesting a relationship between suicidal ideation and low cognitive function in adolescence and young adulthood (Naifeh et al, 2017;Rutter et al, 2020). When the relationship between neurocognitive impairments and suicide is examined, it has been reported that some executive functions, especially those related to emotion regulation and decision-making, constitute a permanent defect in information processing that may contribute to the risk of suicidal behavior (Allen et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, in the most of these tests measuring episodic memory and learning, it was observed that, the number of correct responses in adolescents with depression was significantly lower than that of healthy controls, and they answered questions more slowly. Our findings are consistent with the broad literature suggesting a relationship between suicidal ideation and low cognitive function in adolescence and young adulthood (Naifeh et al, 2017;Rutter et al, 2020). When the relationship between neurocognitive impairments and suicide is examined, it has been reported that some executive functions, especially those related to emotion regulation and decision-making, constitute a permanent defect in information processing that may contribute to the risk of suicidal behavior (Allen et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…We are interested in cognitive constraints because they potentially explain the inability of suicidal people to fully consider alternatives and consequences of suicide. The growing empirical literature linking suicidal behavior to cognitive deficits has been recently reviewed and subjected to meta‐analyses (K. J. D. Allen et al, 2019 ; Bredemeier & Miller, 2015 ; Cha et al, 2019 ; Jollant et al, 2011 ; Liu et al, 2017 ; Richard‐Devantoy, Berlim, & Jollant, 2014 ; Richard‐Devantoy et al, 2015 ; Rutter et al, 2020 ; Saffer & Klonsky, 2018 ). Two general patterns can be discerned.…”
Section: Suicide As a Cognitive Failurementioning
confidence: 99%
“…Cognitive deficits have been proposed as candidate "endophenotypes" for research on the genetics of suicide [ 5 ]. The cognitive deficits of suicidal individuals are characterized by "cognitive rigidity" [ 6 ]. In MDD with and without suicidal behavior, deficits in decision-making and processing speed have been observed in several studies [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%